Engaging the Invisible - Jowsey, S; Williams, M (Association for Computing Machinery, 2017)
O-Tū-Kapua [what clouds see] is a Mixed Reality art-science project designed to stimulate young learners engagement with scientific concepts. Through complex, multidimensional narratives, this collaborative project has created a blend space where the interaction of Augmented Reality, physical place, analogue making and digital storytelling, are combined in the creation of a situated, embodied learning experience for primary school children.
Keywords: Art/Science; Participatory Art; Mixed Reality; Place Based Education